Binding of Escherichia coli Does Not Protect Tulane Virus from Heat-Inactivation Regardless the Expression of HBGA-Like Molecules - Li, Qianqian; Wang, Dapeng; Yang, David; Shan, Lei; Tian, Peng (Frontiers in Microbiology, 2017)
Histo-blood group antigens (HBGAs) are considered as receptors/co-receptors for human norovirus (HuNoV). It has been reported that binding of HuNoV-derived virus-like particles (VLPs) to HBGA-like molecules-expressing bacteria increased the stability of VLPs to heat-denaturation (HD). In this study, we tested for HBGA-like-binding-conveyed protection against HD on viral replication using Tulane virus (TV) and Escherichia coli O86:H2 (O86:H2), with E. coli K-12 (K-12) used as a control. Expression of HBGA type B was confirmed by ELISA in O86:H2 but not in K-12. Binding of TV was confirmed by ELISA in O86:H2 (P/N=2.23) but not in K-12 (P/N=1.90). Pre-incubation of TV with free HBGA could completely inhibit its ability to bind to O86:H2 (p=0.004), while producing no significant change in its ability to bind K-12 (p=0.635). We utilized a bacterial-capture-RT-qPCR procedure to confirm that both bacterial strains were capable of binding TV, and that O86:H2 exhibited fivefold greater binding capacity than K-12. Pre-incubation of TV with free HBGA would partially inhibit the binding of TV to O86:H2 (p=0.047). In contrast, not only did pre-incubation of TV with free HBGA not inhibit the binding of TV to K-12, binding was slightly enhanced (p=0.13). The viral infectivity assay allowed us to conduct a direct evaluation of the ability of HBGA-like-bound bacteria to confer HD protection to TV. Prior to inoculate to LLC-MK2 cells, TV was incubated with each bacterial strain at ratios of 1:0, 1:1 and 100:1, then both partially and fully HD. The viral amplification was quantitated by RT-qPCR 48h later. The binding of bacteria to TV reduced viral replication in a dose-dependent matter. We found that neither bound O86:H2 nor K-12 conferred protection of TV against partial or full HD conditions. Partial HD reduction of viral replication was not significantly impacted by the binding of either bacterial strain, with infectivity losses of 99.03%, 99.42%, 96.32%, 96.10% and 98.88% for TV w/o bacteria, TV w/O86:H2 (1:1), TV w/O86:H2 (100:1), TV w/K-12 (1:1), and TV w/K-12 (100:1), respectively. Full HD reduction of viral replication was not impacted by the binding of either bacterial strain, as full loss of infectivity was observed in all cases.